Pengembangan Usaha Jamur Tiram Melalui Diversifikasi Produk Jamur Crispy di Batealit Jepara - M. Sagaf; Desti Setiyowati; R. H. Kusumodestoni; Solikhul Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Oyster mushroom production in Mindahan Kidul Village has the potential to be developed and has high economic value. The prospect of developing the oyster mushroom business is quite large which can be seen from the environmental conditions located on the slopes of Mount Muria and the availability of raw materials for planting media that are easily obtained from abundant sawdust. Partners in the service activity program are MSME AJJ Oyster Mushroom Mindahan Kidul which has problems producing baglog and oyster mushrooms that have not been able to become one of the main sources of income. The products produced are F2 mushroom seeds, baglog, and fresh oyster mushrooms. Beside that, the packaging design is still simple and does not have conventional labels and marketing and inadequate production facilities. The purpose of this community service activity is to provide training and assistance to AJJ Oyster Mushroom partners to develop an oyster mushroom product business as a superior product for the Jepara area. The implementation method uses Participatory Rural Appraisal (PRA). The results of community service activities in the form of PPPUD have carried out various forms of training and assistance to partners. The development of the oyster mushroom product business that has been carried out is the processed crispy oyster mushroom